2008
DOI: 10.1007/s10886-007-9407-x
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal Variation of Phenolic Contents in Flowering Heads of Arnica montana cv. ARBO: a 3-Year Comparison

Abstract: In continuation of our studies of altitudinal effects on secondary metabolite profile of flowering heads from taxa of the Asteraceae, we investigated phenolic contents and radical scavenging potential from cultivated plants of Arnica montana cv. ARBO during the growing seasons 2003, 2004, and 2005. By conducting experiments on potted plants, we excluded that differences in phenolic contents from plants grown at different altitudes were related primarily to differences in soil composition at these sites. To ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 15 publications
10
58
0
2
Order By: Relevance
“…and greenhouse, Sofia region 553 m a.s.l. The positive correlation between altitude and the content of caffeic acid derivatives in A. montana cv Arbo flower heads was reported (SPITALER et al 2006(SPITALER et al , 2008. Higher levels of flavonoids in the extracts of flower heads of ex vitro and in vivo grown plants were observed compared to corresponding leaf extracts.…”
Section: Discussionmentioning
confidence: 78%
“…and greenhouse, Sofia region 553 m a.s.l. The positive correlation between altitude and the content of caffeic acid derivatives in A. montana cv Arbo flower heads was reported (SPITALER et al 2006(SPITALER et al , 2008. Higher levels of flavonoids in the extracts of flower heads of ex vitro and in vivo grown plants were observed compared to corresponding leaf extracts.…”
Section: Discussionmentioning
confidence: 78%
“…When the plants are growing in hilly-terrain (high altitude) low temperature and the sunlight contains enhanced UV-β radiations, which may induced oxidative stresses in the plant, hence the plants overcome from the oxidative stresses need to be synthesis of more UV-absorbing and free radical scavenging phenols in plants. 33 The hilly-terrain low temperature may increase the production of phenolics by enhancing synthesis of phenylalanine ammonia lyase (PAL) in plants, while high altitude and long exposure to sunlight hours with higher UV radiation positively affect the activity of enzyme such as phenolics synthase. 34 Meanwhile, small amounts of hilly precipitation could enhance the defense system of plant against stress factor, leading to an increased phenolic content.…”
Section: Discussionmentioning
confidence: 99%
“…Highest content of phytochemicals (phenols, tannins and alkaloids) was observed in the plants collected from Apharwat with an altitude of 2850m asl. This increase in the phenolic content with increase in altitude may be ascribed as a response of plants to enhanced UV-B radiation and decreased temperatures which elicit amplified biosynthesis of UV-absorbing and antioxidant phenolics in plant [24]. Copaja reported that saponin production is higher at high altitudes where the prevailing environmental conditions are stressful.…”
Section: Discussionmentioning
confidence: 99%